The Integration of Artificial Intelligence with Micro–Nano-Systems: Perspectives, Challenges and Future Prospects - Juvenal Rodríguez-Reséndiz; Marcos Aviles; José M. Álvarez-Alvarado (Micromachines)
Technological advances have allowed various systems to be developed on a small scale [...]